2006
DOI: 10.1097/01.ccm.0000233874.88032.1c
|View full text |Cite
|
Sign up to set email alerts
|

Survey of intensive care physicians on the recognition and management of intra-abdominal hypertension and abdominal compartment syndrome*

Abstract: Significant variation across medical training exists in the management of intra-abdominal hypertension and abdominal compartment syndrome. A significant percentage of intensivists may be unaware of current approaches to abdominal compartment syndrome management including monitoring bladder pressures and decompression laparotomy. Future research and education are necessary to establish clear diagnostic criteria and standards for treatment of this relatively common life-threatening disease process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 51 publications
(27 reference statements)
7
57
0
6
Order By: Relevance
“…Among them, intravesical pressure measurement is the generally accepted method in the diagnosis. Two previous studies clearly showed that health practitioners were inadequate in measuring and interpreting IAP in the diagnosis of IAH and ACS (13,14). More practical and easily interpretable methods are essential for detecting IAH before it progresses to ACS.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, intravesical pressure measurement is the generally accepted method in the diagnosis. Two previous studies clearly showed that health practitioners were inadequate in measuring and interpreting IAP in the diagnosis of IAH and ACS (13,14). More practical and easily interpretable methods are essential for detecting IAH before it progresses to ACS.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the reported ESD perforation rate is 7% for cases involving the esophagus, 4% for cases involving the stomach, and 5% for cases involving the colorectum [10,14,15]. Perforation can cause peritonitis and mediastinitis, and possibly also thromboembolism due to blood flow congestion (compartment syndrome) when significant pneumatic leakage results in excess internal pressure [19][20][21][22][23][24]. It is anticipated that such associated problems will be minimized by further use of CO 2 insufflation.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,48,49 Thus, ACS is a clinically important problem in critically ill patients that can be ameliorated by early recognition of IAH and appropriate medical or surgical intervention for IAH and impending ACS. Bedside critical care nurses are responsible for accurately measuring IAP and alerting physicians about important observed changes.…”
Section: Resultsmentioning
confidence: 99%